Middle Ear Effusion in Children: Review of Recent Literature - Ashoor, A. (Medknow Publications & Media Pvt Ltd, 1994)
Middle Ear Effusion (O.M.E.) is the commonest ear problem among children, with a peak at the age of 2 years. Incidence varies according to geographical location and race variation, environmental and socio-economic factors. The disease is characterized by accumulation of semi-sterile secretion in the middle ear. It is usually due to either a dysfunction of Eustachian tube or of the mucociliary system or both. The most common presenting symptoms are mild to moderate conductive hearing loss, attacks of earache, and deterioration in school. The diagnosis is based on history, clinical findings and hearing assessments. In general, treatment is classified as conservative and surgical. Early screening and health education are the recent concepts advocated, for early detection.